A Comparison of four routinely used Vitamin D automated immunoassays and an evaluation of clinical impact of arbitrary cut-off levels: Comparison of four Vitamin D immunoassays - Broz, Pavel; Windrichova, Jindra; Fuchsova, Radka; Topolcan, Ondrej; Pecen, Ladislav; Mayer, Otto; Kucera, Radek (Journal of Medical Biochemistry, 2020)
Aim: To compare four automated immunoassays for the measurement of vit25OHD and to assess the impact on the results obtained from a healthy population. Methods: We analysed 100 serum samples on Unicel DxI 800 (Beckman Coulter), Architect i1000 (Abbott), Cobas e411 (Roche) and Liaison XL (DiaSorin). A Wilcoxon signed-rank test was used to compare the different methods’ values and method comparison was further performed using Spearman’s rank correlation, as well as linear and Passing-Bablok regression. In order to clinically categorise the obtained values, results were categorised into the following groups: 0–25 nmol/l, 25–50 nmol/l, 50–75 nmol/l and above 75 nmol/l and compared. The percentage of samples below 75 nmol/l and below 50 nmol/l was then calculated for every method. Results: According to paired comparisons, each method differs from others (P<0.0001) except Cobas vs. Architect, which do not show a statistically significant difference (P=0.39). The strongest correlation was found between Liaison and Architect (r=0.94, P<0.0001). The percentage of samples below the reference value of 75 nmol/l were: 70% (Abbott), 92% (Liaison), 71% (Cobas) and 89% (Unicel). The percentage of samples below the value of 50 nmol/l were: 17% (Abbott), 55% (Liaison), 28% (Cobas) and 47% (Unicel). Conclusion: The observed differences stem from the use of different analytical systems for vit25OHD concentration analysis and can result in different clinical outcomes. The reference ranges should be established for each assay in accordance with data provided by the manufacturer or in the laboratory, in accordance with proper standardisation.